Gasto público en telecomunicaciones y el acceso a los servicios de internet en la región Loreto 2012 - 2021 - Fasanando Cerrón, Greys (2023)
The objective of this research work is to determine the estimated effect of public spending on Osiptel and public spending in the budget program access and proper use of telecommunications services on access to internet services in Loreto 2012-2021, with the purpose of contributing to the reduction of the communication infrastructure gap since the public telecommunications service is of high social interest. The research was of a quantitative type, correlational-applied level and non-experimental design with longitudinal data. After applying the OLS regression for time series, it was found that as public spending accrued from Osiptel increases by 1%, the percentage of the population with access to Internet services in Loreto grows by 0.23% in the next period; likewise, the existence of a moderate direct relationship between the variables (r=0.6065). Otherwise, the public expenditure accrued in the program does not present any significant effect on the dependent variable.